Organized crime and wage inequality. (11th December 2019) - Pi, Jiancai; Zhang, Pengqing
Abstract: This paper stresses the role of industrial organization of crime, and explores how organized crime affects wage inequality. We find that, when only unskilled workers (or both skilled and unskilled workers) engage in organized crime, an increase in the number of criminal groups will increase wage inequality if (1) the skilled sector is more capital intensive than the unskilled sector, and (2) the price elasticity of demand for the skilled product is large enough. However, when there are only skilled workers engaging in organized crime, condition (1) is sufficient to widen wage inequality, irrespective of the price elasticity.